Evaluation of Mexican poverty reduction policies under the COVID-19 pandemic impacts - Gou Shuying; Gou Shuying; Liu Xuedong (Frontiers Media S.A., 2022)
From 2019 to 2020, the Mexican economy declined for two consecutive years, especially in the last one when it was hit by a decline of 8.4% before the COVID-19 pandemic impacts which was not only one of the worst in the OECD club, but also the deepest economic recession since 1932 in the national history. At the same time, both the number of people in poverty and poverty rate in 2020 have increased compared with those registered in 2018. Through the analysis, we can find that the current Mexican government has increased the intensity and scope of the implementation of social relief policies adhered to the principal of "for the good of all, first the poor (Por el bien de todos, Primero los pobres)." However, in the context of recession caused by the COVID-19, neither the general decrease in residents' income could be avoided, nor the number of people in poverty has been reduced. Besides, in accordance with the benefits obtained by the distinct household deciles based on the income and expenditure survey published by INEGI, it showed that the implementation of government relief measures has relatively reduced the support for the low-income people and further aggravated the deterioration of poverty due to its indifferent application with respect to high-income households and the low-income ones. Therefore, the deficiencies in the response implemented in the face of the epidemic, especially poverty alleviation actions and social relief policies, have further enhanced the poverty problem at least partially. In this sense, recover and improve the economic growth rate as soon as possible will not enough to reduce the poverty, and it should be accompanied by the necessary adjustments in the poverty alleviation measures and social relief policies, especially with a focalized approach inclined to the low-income segments of the population.